2011
DOI: 10.1007/s10637-010-9622-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effects of tolfenamic acid against esophageal tumorigenesis in rats

Abstract: The primary objective of this study is to identify small molecules that target critical transcription factors for potential application in the chemoprevention of esophageal cancer. Specificity proteins (Sp) play a critical role in the growth and metastasis of several malignancies including esophageal cancer. Researchers at the M. D. Anderson Cancer Center Orlando Cancer Research Institute have reported previously that tolfenamic acid (TA) inhibits cancer cell proliferation and tumor growth through the degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…This therapeutic strategy provides promising activity and better tolerance than standard cytotoxic therapies currently being used in pancreatic cancer. Cur [48] and TA [52] have been tested (individually) for their chemopreventive properties and both of these agents showed a positive response in animal models. Cur exhibited cancer prevention in a clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic strategy provides promising activity and better tolerance than standard cytotoxic therapies currently being used in pancreatic cancer. Cur [48] and TA [52] have been tested (individually) for their chemopreventive properties and both of these agents showed a positive response in animal models. Cur exhibited cancer prevention in a clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Even though our previous studies using rats showed limited toxicity of TA [38], this is the first study assessing the toxicity in detail, achieved through putting together the results of animal growth patterns, blood chemistry and organ histopathology. All these results showed limited cytotoxicity and GI effects.…”
Section: Discussionmentioning
confidence: 99%
“…TA has been studied in pre-clinical models for adult (pancreatic [26,27], lung [28], esophageal [14,29], ovarian [30], prostate [31,32], and colon [33,34]) cancers and pediatric (leukemia [35], neuroblastoma [36], and medulloblastoma [37]) malignancies. Experimental results from our laboratory also showed a chemopreventive effect by this drug in an animal model of esophageal cancer [29,38]. TA exhibits anticancer and chemopreventive activities primarily via inhibiting specificity protein (Sp) transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Tolfenamic acid when combined with mithramycin A, another Sp1 inhibitor, results in synergistic anticancer effect [93]. Tolfenamic acid has been successfully shown both in vitro and in vivo mouse models to inhibit growth of several different cancers including esophageal, oral, lung, breast, neuroblastoma, cervical, ovarian, colorectal, and prostate cancer [97][98][99][100][101][102][103][104][105].…”
Section: Sp1 Targeted Therapy In Pancreatic Cancer (Pre-clinical Studmentioning
confidence: 99%